Pengaruh Struktur Modal Dan Pertumbuhan Penjualan Terhadap Kinerja Keuangan - Apriyani, Ismi; Dewi, Intan Pramesti (Cattleya Darmaya Fortuna, 2025)
This study's overarching goal is to identify the relationship between sales growth, capital structure, and financial success. Quantitative studies fall under this category of study. We focus on consumer companies that aren't part of cyclical industries and are listed on the Indonesia Stock Exchange (BEI) from 2019 to 2023 in our research. Revenue growth and capital structure are seen as independent variables in this research, with financial performance serving as the dependent variable. Purposive sampling is the method used in the sampling procedure. using a sample of 89 businesses over five years of monitoring, so the totally is 445. However, the observations are 310 because there are 80 outliers and 55 incomplete financial reports. Multiple linear regression analysis and statistical analysis were used as analytical methods in this research. This analysis method is calculated using a statistical tool, namely EViews Version 12.